Micro-Ribonucleic Acid-216a Regulates Bovine Primary Muscle Cells Proliferation and Differentiation via Targeting SMAD Nuclear Interacting Protein-1 and Smad7 - Yang, Zhaoxin; Song, Chengchuang; Jiang, Rui; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong (Frontiers in Genetics, 2019)
MicroRNAs (miRNAs), belonging to a class of evolutionarily conserved small noncoding RNA of ∼22 nucleotides, are widely involved in skeletal muscle growth and development by regulating gene expression at the post-transcriptional level. While the expression feature and underlying function of miR-216a in mammal skeletal muscle development, especially in cattle, remains to be further elucidated. The aim of this study was to investigate the function and mechanism of miR-216a during bovine primary muscle cells proliferation and differentiation. Herein, we found that the expression level of miR-216a both presented a downward trend during the proliferation and differentiation phases, which suggested that it might have a potential role in the development of bovine skeletal muscle. Functionally, during the cells proliferation phase, overexpression of miR-216a inhibited the expression of proliferation-related genes, reduced the cell proliferation status, and resulted in cells G1 phase arrest. In cells differentiation stages, overexpression of miR-216a suppressed myogenic maker genes mRNA, protein, and myotube formation. Mechanistically, we found that SNIP1 and smad7 were the directly targets of miR-216a in regulating bovine primary muscle cells proliferation and differentiation, respectively. Altogether, these findings suggested that miR-216a functions as a suppressive miRNA in development of bovine primary muscle cells via targeting SNIP1 and smad7.